Filariasis in the new millennium (Medical Journal of Indonesia, 2001)
The lndonesian national filariasis eradication program in its pursuit in obtaining microfilarial rates below 1% in filariasis endemic locations was on its right track until the monetary crisis started 3 years ago. This crisis which is not over yet at present is complicated by unstable public safety causing population shifts where people from filaria endemic locations seek refuge in non-endemic areas. This updated review will hopefully serve as a timely reminder to our physicians and health workers especially on the mode of filarial transmission as well as on its clinical presentations and presently accepted ways of manaqement. This paper also will serve as an introduction into the present breakthroughs in this new millenium as noted in the field of diagnostics and simplified mass treatment schedules making it possible for the elimination of lymphatic filariasis as a public health problem. A global alliance under the guidance of the World Health Organization with support of the multinational pharmaceutical companies for providing free expensivemedication as needed. The WHO also cooperates closely with the Tropical Diseases Research task forces of Filariasis Intervention Research and of Product Development, that in the end will provide the means to eradicate this disease for once and forever from the face of the earth. (Med J Indones 2001; 10: 191-6)